A systematic literature review of the factors affecting smartphone user threat avoidance behaviour. (2nd June 2020) - Butler, Rika
Abstract : Purpose: There is a need for behavioural research within the smartphone context to better understand users' behaviour, as it is one of the reasons for the proliferation of mobile threats. This study aims to identify the human factors that affect smartphone users' threat avoidance behaviour. Design/methodology/approach: A structured literature review (SLR) was applied to answer the research question. A total of 27 sources were analysed, from which 16 codes emerged. After synthesis, six themes transpired. Findings: Six factors were identified as drivers and/or challenges of smartphone users' threat avoidance behaviour, namely, knowledge and awareness, misconceptions and trust, cost and benefit considerations, carelessness, perceived measure effectiveness and the user's perceived skills and efficacy. Research limitations/implications: The results can encourage and provide a starting point for further research on human behaviour to improve smartphone user behaviour. Practical implications: The mobile industry should focus on eradicating common misconceptions and undue trust in mobile security that is prevalent among smartphone users and make cost effective and usable interventions available. Training and awareness programs should be updated to include the factors that were identified in this study to affect smartphone users' threat avoidance behaviour. In addition to improving users' declarative knowledge concerning available smartphone measures and tools, procedural knowledge should also be improved to ensure proper use of available protective measures. Users should realise the importance of staying updated with evolving smartphone technology and associated threats. Originality/value: This study acknowledges and supports the notion that addressing human behaviour is crucial in the fight against mobile threats. It addresses the need for behavioural research to analyse the factors that drive smartphone user behaviour. Furthermore, it uses and documents the use of a SLR, a research technique often unfamiliar among information security researchers.